Empowerment of Environmentally Conscious Groups in Processing Organic Waste into Multipurpose Eco Enzymes: Pemberdayaan Kelompok Sadar Lingkungan Dalam Pengolahan Sampah Organik Menjadi Eco Enzym Serbaguna - Mubarak*, Adil; Syamsir , Syamsir Syamsir; Frinaldi, Aldri; Syolendra, Dwi Finna (Universitas Lancang Kuning, 2024)
The issue of environmental pollution due to waste is the most complex problem currently being faced by the nagari government. The high level of waste generated from trading activities makes the entire length of the Nagari market alley dirty and smelly due to the accumulation of vegetable and fruit waste. Nagari Sikabau with a population of 9,268 people spread across 11 jorongs has the potential to generate household waste of up to 5 tons per day. Efforts to deal with waste by transporting waste to final disposal sites (TPA) carried out by waste transport officers cannot solve the problem. Guidance through education, training and assistance in processing organic waste into multi-purpose eco enzymes for the environmentally conscious group (pokdarling) of Nagari Sikabau youth has increased literacy, motivation and skills to make changes in waste management to the community-based waste management paradigm. Currently, Pokdarling as a community has become a pioneer for the Nagari Sikabau Community and is able to produce eco enzyme liquid which will be converted into economically valuable products.